Pengaruh kejelasan sasaran anggaran, pengendalian akuntansi dan sistem pelaporan terhadap akuntabilitas kinerja pemerintah - Eko Setiawan; Andreas '; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to obtain empirical evidence on the effects of partial and simultaneous clarity budgetary targets, accounting controls and reporting systems for accountability of government performance of Pelalawan Local Government.Population and sample of the study was the head of department / agency / office and head section / sub section on education in finance on 30 SKPD Pelalawan Data collected by distributing questionnaires to heads of 60 departments / agencies / offices and the head section / subsection finance . Data processing is done by using multiple regression analysis .The results show that the budget goal clarity and accounting controls a significant effect on performance accountability of government agencies , while reporting system does not affect the performance accountability of government agencies . The magnitude of the effect of independent variables on the dependent variable is equal to 96.4 % . 3.6 % means there are other variables that affect the dependent variable .Keywords : Budget Goal Clarity , Control Accounting , Reporting Systems , Performance Accountability .